Examination of the prevalence of stimulus overselectivity in children with ASD. Issue 1 (24th November 2014) - Rieth, Sarah R.; Stahmer, Aubyn C.; Suhrheinrich, Jessica; Schreibman, Laura
Abstract Many individuals with autism spectrum disorders (ASD) display stimulus overselectivity, wherein a subset of relevant components in a compound stimulus controls responding, which impairs discrimination learning. The original experimental research on stimulus overselectivity in ASD was conducted several decades ago; however, interventions for children with ASD now typically include programming to target conditional discriminations in ways that might minimize the prevalence of stimulus overselectivity. The present study assessed 42 children who had been diagnosed or educationally identified with ASD using a discrimination learning assessment. Of these 42 children, 19% displayed overselective responding, which is a lower percentage than that seen in early research. Possible explanations for this decreased percentage, implications for intervention, and future directions for research are discussed.